The impact of inflation targeting: Testing the good luck hypothesis - Federico Ravenna; Marcus Mølbak Ingholt (Danmarks Nationalbank, 2020)
Starting in the mid 1980s, the level and volatility of inflation decreased across industrial countries. The inflation stabilization can be explained by a shift in monetary policy or by a lucky period of low volatility in business cycle shocks. To test the "good luck hypothesis", we examine the inflation experience of Canada, one of the earliest and most successful adopters of an inflation targeting monetary policy. We Kalman-filter the historical structural shocks consistent with an estimated DSGE model. The estimated shocks are used to build counterfactual histories. The good luck hypothesis can explain only a minor portion of the change in the path and volatility of inflation after the shift in policy. Most of inflation and output stabilization is accounted by the impact on expectations. Unconditionally, the inflation targeting policy does not improve on the previous policy in terms of inflation volatility, but supports a more favorable trade-off, reducing substantially output volatility.
Keywords: E42; E52; E58; 330; Business cycle shocks; Kalman filter; Credibility; Inflation targeting